(untitled) (Medico Legal Update, 2021)
The present study has been carried out at the Women’s and Educational Children’s Hospital in the city of Samawa to determine the level of oxidative stress indicators and level ferritin. 66 samples of a patient with beta-thalassemia major were collected and observation of some clinical signs was followed, the group of a patient was divided into two subgroups according to the splenectomy, Group One (G1)) Included 52 samples from beta-thalassemia major patients, type non-splenectomy, (G2) included 14 samples from thalassemia patients splenectomy and 34 samples were collected from healthy males as control samples (C) to measure the level the activity of Catalase enzyme (CAT) and concentration levels of malondialdehyde MDA as oxidative stress indicators by using the Spectrophotometer and level ferritin using vidas. The results showed a significant decrease (p<0.05) in the efficacy of catalase and a significant increase (p<0.05) in the level of the MDA and level ferritin in beta-thalassemia major patients compared to control group.